Treatment Motivations and Expectations in Patients with Actinic Keratosis: A German-Wide Multicenter, Cross-Sectional Trial - Steeb, Theresa; Wessely, Anja; Von Bubnoff, Dagmar; Dirschka, Thomas; Drexler, Konstantin; Falkenberg, Conrad; Hassel, Jessica C.; Hayani, Kinan; Huening, Svea; Kaehler, Katharina C.; Karrer, Sigrid; Krammer, Christian; et al. (Journal of Clinical Medicine, 2020)
Patient-centered motives and expectations of the treatment of actinic keratoses (AK) have received little attention until now. Hence, we aimed to profile and cluster treatment motivations and expectations among patients with AK in a nationwide multicenter, cross-sectional study including patients from 14 German skin cancer centers. Patients were asked to complete a self-administered questionnaire. Treatment motives and expectations towards AK management were measured on a visual analogue scale from 1-10. Specific patient profiles were investigated with subgroup and correlation analysis. Overall, 403 patients were included. The highest motivation values were obtained for the items "avoid transition to invasive squamous cell carcinoma" (mean +/- standard deviation; 8.98 +/- 1.46), "AK are considered precancerous lesions" (8.72 +/- 1.34) and "treating physician recommends treatment" (8.10 +/- 2.37; p < 0.0001). The highest expectation values were observed for the items "effective lesion clearance" (8.36 +/- 1.99), "safety" (8.20 +/- 2.03) and "treatment-related costs are covered by health insurance" (8.00 +/- 2.41; p < 0.0001). Patients aged >= 77 years and those with >= 7 lesions were identified at high risk of not undergoing any treatment due to intrinsic and extrinsic motivation deficits. Heat mapping of correlation analysis revealed four clusters with distinct motivation and expectation profiles. This study provides a patient-based heuristic tool for a personalized treatment decision in patients with AK.
CRIS-Team WoS Importer:2020-06-26